Effect of light stress on the adrenal cortex of the Algerian saharan rodent Gerbillus tarabuli: Microscopic and morphometric changes - Derbouz Rouibate, Amina; Benhafri, Nadir; Benkali, Belkis; Benkali, Baraa; Ouali-Hassenaoui, Saliha; Dekar-Madoui, Aicha (Acta Biologica Szegediensis, 2025)
In today's world, stress is prevalent, including the widespread exposure to high levels of light at night. This disruption of the natural light-dark cycle significantly affects circadian rhythms, making it a major source of physiological stress. The aim of this study was to analyze the effects of a modified light-dark cycle, as a model of stress, on the adrenal gland morphology in the wild desert rodent Gerbillus tarabuli. The animals were divided into two groups of 10 gerbils each. The first group, considered as the control group, was maintained under a standard 12-hour light/12-hour dark cycle. The second group, referred to as the stressed group, was exposed to a disrupted light-dark cycle, switching between a standard 24-hour cycle and a modified cycle with a 20-hour light phase every other day for three months. Following the experimental period, the adrenal glands were removed and processed for histomorphometric analysis. In the stressed group, various histological changes were noticed in the form of loss of normal adrenal architecture. Morphometric results demonstrated a significant increase (P<0.001) in the total length and area of the adrenal gland, as well as in its three cortical zones (glomerulosa, fasciculata, and reticularis). We also observed an increase in the diameter of cells and their nuclear area within the adrenal cortex, except for the cells in the zona fasciculata, which demonstrated a decrease in size (P>0.05). The findings demonstrate that the histological organisation of the adrenal gland is directly affected by exposure to light stress, highlighting the significant impact of circadian disruption on adrenal structure and function.